The Integration of Biblical Authority in the Construction of the Theological Education Curriculum: Theological and Pedagogical Analysis - Edison Edison; Erikana Laia; Temaziso Halawa; Linusman Hulu; Tema'aro Zai (Proceeding of The International Conference on Religious Education and Cross - Cultural Understanding, 2026)
This research aims to analyze the integration of biblical authority in the construction of the theological education curriculum through a theological and pedagogical approach. The authority of the Bible as the normative and final word of God has a central role in the formation of doctrine, ethics, and practices of church life, so it should be the main foundation in the development of the theological education curriculum. In practice, however, there is a tendency that the construction of the curriculum is more influenced by modern academic and pedagogical approaches without adequate integration into biblical theological foundations. This study uses a qualitative method with a literature study approach that analyzes various sources of systematic theology and Christian education theory. The results of the study show that the integration of biblical authority in the theological education curriculum can be carried out through three main aspects, namely: (1) the placement of the Bible as a normative source in the entire curriculum structure, (2) the integration of theological values in learning design, and (3) the development of pedagogical models oriented towards spiritual formation and character. The findings of this study confirm that the construction of a theological education curriculum rooted in biblical authority not only results in academic competence, but also shapes spirituality, integrity of faith, and readiness for ministry. Thus, this research makes a conceptual contribution in developing an integrative theological education curriculum model between theological and pedagogical dimensions.